Development of a method to model the mixing energy of solutions using COSMO molecular descriptors linked with a semi-empirical model using a combined ANN-QSPR methodology. (12th October 2020) - Sosa, Adriel; Ortega, Juan; Fernández, Luis; Palomar, José
Highlights: Relationships between the model parameters and the molecular interactions is assumed. A link is established between the model-parameters/COSMO molecular descriptors pairs. A combined ANN-QSPR procedure is used to quantify the relation parameter/ descriptor. The work shows the feasibility of the methodology developed. Abstract: A methodology linking the interaction parameters of a semi-empirical model to COSMO molecular descriptors to represent the h E ( x ) is presented. A database of 4395 values of ester-alkane is used to check the procedure. Relationships are established for the model coefficients, a i1, i2, …ip, although only for a 12 and for a second parameter k 21, which governs the asymmetry of the representation of the mixing process. A discretization of the σ-profile and its statistical moments constitute two descriptors, as a vector, S σ - p r o f i l e j and S σ - m o m e n t p, for a 12 . A third molecular descriptor/vector, is described for k 21, based on the divergence of Kullback-Leibler and the molecules size, which is presented for the first time as: S R σ - p r o f i l e = A 1, A 2, D KL [ p 1 ( σ ) | | p 2 ( σ ) ], D KL [ p 2 ( σ ) | | p 1 ( σ ) ] The clustering of systems in a a 12 / k 21 -space is predictable with molecular descriptors in relation to their main interactions. An ANN-QSPR binomial estimates the parameters a 12 and k 21 from molecular descriptors. The methodology generalizes the procedure, acceptably representing the energetic effects of solutions ( R 2  > 0.9).